Seismic fragility of lateral force resisting systems under near and far-fault ground motions. (2016) - Soltangharaei, V.; Razi, M.; Vahdani, R.
In this paper, the effect of near- and far-fault ground motions on the seismic performance of buckling restrained braced frames (BRBFs) and special moment resisting frames (SMRFs) are evaluated. Incremental dynamic analyses are employed to quantify the response parameters of the sample structures (two sets of three frames), and fragility curves are derived. Comparison of the results for near-fault records are made with ordinary records. The fragility curves are developed for life safety (LS) and collapse prevention (CP) performance levels. Based on the results, the average values of PGA corresponding to 10% probability of collapse are equal to 0.50 g and 0.42 g, for BRBF structures (CP limit state), for far and near-fault ground motions, respectively, These values are equal to 0.55 g and 0.45 g, for SMRF counterparts. It reveals that seismic performance of BRBF structures against near-fault records is similar to SMRF structures, or even better in some cases.